Mass-spectrometric investigations of gas evolution - Asnis, Yu.A.; Baranskii, P.I.; Babich, V.M.; Zabolotin, S.P.; Ptushinskii, Yu.G.; Sukretnyi, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Method of mass-spectrometry with time-of-flight recording of the desorbed products was used to study the gas evolution of impurities from the subsurface layer of Si crystals molten by the electron beam (of ~2 mm² area) in the vacuum of 10⁻⁵ – 10⁻⁷ Pa. It is shown that irrespective of vacuum level, oxygen (m = 32) and hydrogen (m = 2) in the molecular state as well as Si atoms (m = 28) are registered as the main components of gas evolution in the mass-spectrum in melting. With longer time of the subsurface layer exposure in the molten state, an indication of CO evolution (fragment peak m = 12) appears in the mass-spectrum. There is, however, a ground to believe that this is the consequence of gas evolution from the fixtures, and not from the Si sample. Features of gas evolution were revealed at the initial stage of heating and melting of Si sample, depending on the previous heat-treatment of the sample. If melting the subsurface zone proceeds after contact with the atmosphere, initial peaks of evolution of oxygen and hydrogen molecules and Si atoms are observed. These are partially weakened with further keeping the sample in the molten state. In our opinion, such a peak is due to contamination of the surface at such a contact. A long-term exposure in vacuum of a sample cooled after melting does not lead to appearance of the above peak at subsequent melting.